Treatment of meloxicam overdose in a dog via therapeutic plasma exchange. Issue 4 (8th May 2017) - Walton, Stuart; Ryan, Kirk A.; Davis, Jennifer L.; Acierno, Mark
Abstract: Objective: To describe the treatment of a meloxicam overdose in a dog with therapeutic plasma exchange (TPE). Case Summary: A 6‐month‐old female Bulldog, presented for routine laparoscopic ovariectomy. Postoperatively the dog received an accidental overdose of meloxicam (1 mg/kg IV [intravenously]). The patient was treated with supportive medical therapy and TPE over 210 minutes achieving 1.2 plasma volume exchanges. During therapy, heparinized blood and effluent samples were collected. Meloxicam concentrations were determined in the samples by high pressure liquid chromatography. Post TPE, the dog continued to receive supportive medical therapy and was discharged 48 hours after the overdose. The dog remained asymptomatic for meloxicam intoxication. Follow‐up rechecks at 1 and 6 weeks were unremarkable with no further treatment required. New or Unique Information: This report describes the successful use of TPE adjunctively following an acute meloxicam overdose. An 82% reduction of plasma meloxicam concentration was achieved over 210 minutes. Twenty‐four hours after therapy, a 47% sustained reduction of plasma meloxicam was measured after redistribution of drug between body compartments.